The Development of Intensive English Research Writing Training Model to Encourage International Publishing for University Lecturers (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The objectives of the research entitled “the development of intensive English researchwriting training model to encourage international publishing for university lecturers”were to: 1) develop intensive English research writing training model to encourageinternational publishing for university lecturers and to assess the effects of the use ofintensive English research writing training model as following methods: 1) to assessEnglish writing skill about research for international publishing, 2) to assess researchcompetency of university lecturers, 3) to assess the language lecturers’ satisfactiontowards intensive English research writing training model, 4) to assess the research fullpaper’s quality of the university lecturers, and 5) to follow up efficiency of universitylecturer’s research from a number of researches published in an international conferenceor a journal. The population was 42 university lecturers at College of General Educationand Languages, Thai-Nichi Institute of Technology, Bangkok, Thailand. The sampleswere 17 language lecturers derived through volunteer random sampling techniques. Theresearch instruments comprised of tests, questionnaire, interview forms, and assessmentforms. Data were analyzed in terms of percentage, means, standard deviation, t-test, andcontent analysis. Research findings were found as follows: 1) the intensive Englishresearch writing training model to encourage international publishing for universitylecturers was proved to be effective and verified as by experts. 2) The empirical data thatsupported the effectiveness of the intensive English research writing training model wereas follows: 1) regarding to the university lecturers, their English writing skill aboutresearch for publishing in international conference before and after the implementation ofthe intensive English research writing training model were statistically significantdifferent at the .05 level; 2) The research competency of university lecturers alsodemonstrated a high level of competency on research; 3) They were satisfied with theintensive English research writing training model at the highest level; 4) Regarding to thequality of research full paper, it was found that a number of research full papers whichwere verified from experts were at a good level; and 5) Regarding to follow up efficiencyof university lecturer’s research from a number of research published in an internationalconference, it was found that there were 17 research papers (out of 17) which werepublished in international conference after the implementation of the intensive Englishresearch writing training model.